Thinking about integrated supply chain technology as an enabler for local businesses? - Sidah Idris; Al Nasrie Weli; Charlie Albert Lasuin; Siti Hajar Samsu; Nelson Lajuni (Penerbit UUM, 2021)
Business activities were significantly hampered when the Movement Control Order (MCO) was issued in response to the COVID-19 epidemic. The ramifications of these MCO series have a direct and indirect impact on the bulk of company activities. As a result of the economic crisis, it triggered a severe depression. As a result, they looked for additional ways to maintain and extend their activities, including using the Internet as a means of conducting business. The goal of this research is to determine the value of the innovative value chain as well as the role of integrated supply chain technology in improving the efficiency of enterprises' supply chains. Standardized questionnaires were provided to local business owners in three major divisions of Sabah, namely Kota Kinabalu, Sandakan, and Tawau in order to achieve this purpose. The survey got 125 usable replies from large, medium, and small enterprises that have been in existence for more than ten years. The main findings of three variables, namely idea generation, concept conversion, and diffusion of innovation, encouraged SCT adoption among Sabah's small businesses. The interaction effect revealed that Integrated SCT does, in fact, act as a mediating component in the financial performance relationship. As a result, COVID-19 is a game changer for everyone particularly local businesses and governments because the outbreak pushed the implementation of information technology, such as supply chain integration.